Correction of CSF motion artifact on MR images of the brain and spine by pulse sequence modification: clinical evaluation. - Szeverenyi, N M; Kieffer, S A; Cacayorin, E D (American Journal of Neuroradiology, 1988)
A modification of the standard spin-echo pulse sequence designed to suppress motion artifacts was clinically evaluated on T2-weighted MR images of the cervicocranial region. A retrospective study involving 40 patients, half of whom were examined with a standard T2-weighted multislice spin-echo sequence and half of whom were examined with a gradient waveform modification of the same sequence, uniformly demonstrated restoration of CSF signal intensity on images obtained with the gradient modified sequence. The cervical subarachnoid spaces, cisterna magna, medullary cistern, pontine cistern, fourth ventricle, and aqueduct were more consistently and brightly represented. However, the phase-encoding artifacts arising from CSF motion were not significantly reduced by using the gradient waveform modified pulse sequence. Digital subtraction of an image obtained with the standard sequence from an image of the same slice with the gradient modified sequence provides a direct image representation of CSF flow.